Anti-Competitive Effect in the Context of Economic Competition Concepts - Dimitrova, Emilia (Yearbook of the Law Department, 2019)
The anti-competitive effect is the hallmark of market dominance abuse. Neither the European Union Competition Law nor the Bulgarian Competition Law contains a legal definition of this term. It is linked to the term “competition“. The concept of competition is borrowed from economics. The interrelationship between market dominance and market dominance abuse outlines the subject-matter of this article. The present research examines the essence of the anticompetitive effect in the context of those economic concepts of competition that underlie the doctrines of market dominance.